Shock-induced persistent contact and synchronous re-levitation control in an AMB-rotor system. (15th January 2022) - Su, Yixin; Gu, Yongpeng; Keogh, Patrick S.; Yu, Suyuan; Ren, Gexue
Highlights: Bi-stable responses in an active magnetic bearing rotor system are investigated. Shock-induced persistent contact between the rotor and touchdown bearing was observed. The analytical solution for synchronous rubbing of a general AMB-flexible rotor was proposed. The dynamic model reproduces the bi-stable and the persistent contact responses. Two controller are proposed and validated to re-levitate the rotor automatically. Abstract: Active magnetic bearings (AMBs) have limited dynamic load capacity due to magnetic saturation. Hence, large external disturbances (such as shock loads) may cause contact between the rotor and touchdown bearings (TDBs), which may evolve into complex dynamic behaviour and damage the machine. This paper considers the shock responses of a rotor and viable re-levitation control options when the AMB is still functional. Bi-stable responses and shock-induced persistent forward rubbing were observed in an experimental AMB-flexible rotor facility and its numerical model. The analytical solution for steady synchronous motions with rubbing of a general AMB-flexible rotor system was proposed. The standard control action for a contact-free rotor state would not be appropriate due to phase changes and the displacement amplitude differences in the frequency responses. To destabilise the persistent contact responses and restore contact-free levitation, open-loop phase search based synchronous compensation (PSSC) control and synchronous motion compensation (SMC) control are designed, which are activated when a persistent contact is detected. Stability of the control system and the effectiveness of these two re-levitation control methods are verified by simulation and experimental results. It is also found by comparison that the efficiency of PSSC depends on the phase difference (incorrect phases may degrade rotor response), while the SMC consumes more computing effort.